Job Satisfaction, Leadership Style & Personality : A Study Of Childcare Providers In Melaka, Malaysia - Ong, Puay Tee (2005)
Early childhood education is a cruacial period when children's attitude are shaped, formed and fortified by their childcare providers. Unfortunately, to date, no reported research has been carried out on childcare providers and related aspects, for example, job satisfaction. Several reasons are identified for this lack of interest. This current research on childcare centres is an attempt to address this lacuna. Thompson, MvNamara and Hoyle's (1997) situational model of job satisfaction was adopted to explain how categories of variables such as task characteristics, organisational characteristics and individual characteristics combine to relate with job satisfaction. A population study was undertaken on all childcare centres in Melaka. Data collection was carried using questionnaire survey, focus group and individual interviews.